Tourism Management Model to Support Tourists Digital NOMADs Sumui Island, Surat Thani Province - Pattanameteewit, Russarin (Journal of Cultural Analysis and Social Change, 2025)
This study examines the current status of tourist attractions for NOMAD tourists, study the problems of tourist attractions for NOMAD tourists, study the factors affecting the decision to choose Koh Samui as a tourist attraction for NOMAD tourists, study the level of satisfaction of NOMAD tourists with tourist attractions on Koh Samui, and to propose recommendations for the development of Koh Samui as a tourist attraction for NOMAD tourists. This study was a mixed-method research, collecting data from 385 tourists using simple random sampling, tourism experts and tourism agency executives using purposive sampling, and analyzing the data using descriptive statistics, analysis of variance (ANOVA), and multiple regression analysis. The findings reveal that (1) the current status of tourist attractions on Koh Samui for NOMAD tourists is ready in terms of infrastructure, internet connection, a variety of accommodations, and tourist activities that support the lifestyle of this group. (2) The problems of tourist attractions for NOMAD tourists, including infrastructure, environmental management, availability of affordable accommodations, and specific tourism promotion policies, are still important obstacles in developing tourist attractions for this group of tourists to be sustainable and able to support long-term growth. (3) The factors affecting the decision to choose Koh Samui as a tourist attraction for NOMAD tourists include tourist behavior and tourism stimuli. Factors related to tourism perspectives, social factors, and tourism service characteristics (4) The overall marketing mix of Koh Samui development as a NOMAD tourist destination was found to be at a high level. (5) The development model of Koh Samui as a NOMAD tourist destination should take into account several factors that are consistent with the needs of this group of tourists, focusing on the convenience of working remotely, access to technology, and flexible lifestyles, including internet infrastructure, accommodation that supports remote working, leisure and community activities, community facilities, long-term tourism promotion policies.